Macroeconomic Imbalances as Indicators for Debt Crises in Europe - Tobias Knedlik; Gregor von Schweinitz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2011)
European authorities and scholars published proposals on which indicators of macroeconomic imbalances might be used to uncover risks for the sustainability of public debt in the European Union. We test the ability of four proposed sets of indicators to send early-warnings of debt crises using a signals approach for the study of indicators and the construction of composite indicators. We find that a broad composite indicator has the highest predictive power. This fact still holds true if equal weights are used for the construction of the composite indicator in order to reflect the uncertainty about the origin of future crises. – – Europäische Institutionen und Wissenschaftler haben Vorschläge für die Verwendung bestimmter Indikatoren makroökonomischer Ungleichgewichte zur Aufdeckung von Risiken für die Tragbarkeit der Staatsverschuldung in der Europäischen Union unterbreitet. Wir testen, ob die vier vorgeschlagenen Indikatoren-Sets in der Lage sind, Frühwarnsignale für Schuldenkrisen zu senden. Wir verwenden einen Signalansatz zur Analyse der einzelnen Indikatoren und zur Konstruktion von Verbundindikatoren. Es zeigt sich, dass ein breiter Verbundindikator die höchste Vorhersagekraft hat. Dieses Ergebnis wird auch bestätigt, wenn die Indikatoren gleichgewichtet verwendet werden, um die Unsicherheit bezüglich künftiger Krisenursachen abzubilden.
urn:nbn:de:101:1-201108193511
Keywords: C14; E61; E62; F40; 330; macroeconomic surveillance; macroeconomic imbalances; economic governance; signals approach; European Union (EU); European Monetary Union (EMU); Makroökonomische Überwachung; makroökonomische Ungleichgewichte; wirtschaftspolitische Koordinierung; Europäische Union (EU); Europäische Währungsunion